2019
DOI: 10.4236/aim.2019.99048
|View full text |Cite
|
Sign up to set email alerts
|

Dermatophytes Species Isolated of HIV-Infected Patients Identified by ITS-RFLP and ITS Region Sequencing from Triangulo Mineiro, Minas Gerais State of Brazil

Abstract: Dermatomycoses are a group of diseases worldwide distributed and affect skin, hair and nails. Several fungal species can be envolved and keratinophilic fungi belonging to the genera Trichophyton, Microsporum and Epidermophyton are very common. These infections are globally distributed and their incidence has progressively increased. Despite their high incidence, few studies have been carried out in HIV-infected patients, regarding frequency, clinical presentations, and species identification. This study aimed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
1
3
0
1
Order By: Relevance
“…Contradictory to these results, Otike-Odibi et al found that dermatophytosis in HIV-infected patients is often encountered in people with a secondary educational level, and Bragine-Ferreira et al found only a small proportion of dermatophyte infection in PLHIV with a high educational level. 10,13 However, there is a record of similar results with this study, found by Krzyściak et al, who reported that a majority of the population with a lower education is infected with Malassezia. 14 Malassezia infections can be triggered by several factors, such as a hot and humid environment and overcrowded areas.…”
Section: Discussionsupporting
confidence: 88%
“…Contradictory to these results, Otike-Odibi et al found that dermatophytosis in HIV-infected patients is often encountered in people with a secondary educational level, and Bragine-Ferreira et al found only a small proportion of dermatophyte infection in PLHIV with a high educational level. 10,13 However, there is a record of similar results with this study, found by Krzyściak et al, who reported that a majority of the population with a lower education is infected with Malassezia. 14 Malassezia infections can be triggered by several factors, such as a hot and humid environment and overcrowded areas.…”
Section: Discussionsupporting
confidence: 88%
“…The dermatophytes are a group of keratinophilic ascomycetes from the family Arthrodermataceae . Traditional procedures for fungal systematics based on macro and micro‐morphology of fungi in culture media, physiological and biological traits and ecological niche have limited reliability for assigning dermatophytes to species level or inferring their relationships 1‐3 . Therefore, phylogeny of the group has been studied by molecular methods.…”
Section: Introductionmentioning
confidence: 99%
“…Análisis estadístico: Se ubica en un enfoque cualicuantitativo, cualitativo ya que se fundamentó en la revisión de la literatura relacionada para comprender el fenómeno estudiado, y es cuantitativo porque se utilizó la recolección y análisis estadístico para probar la hipótesis, se calculó los porcentajes y frecuencias para determinar el nivel de cumplimiento de la investigación (Bragine-Ferreira et al, 2019), (Gnat et al, 2020).…”
Section: Entrega De Resultadosunclassified